Five Hundred Days of Farsi Twitter - Layla Hashemi; Steven Wilson; Constanza Sanhueza (Journal of Quantitative Description: Digital Media)
International media was quick to dub the Iranian Green Movement a “Twitter revolution” when it erupted in the summer of 2009. State violence against protestors was captured in real time and broadcast worldwide on social media, providing an early example of a regime's helplessness at locking down a narrative in the face of ubiquitous smart phones. Over a decade later, nearly all foreign social media remain officially blocked in Iran, yet Iranians evade state suppression and remain connected to the global community. This article introduces a new dataset of all Farsi-language tweets since September 2019. To date, this amounts to the full text and associated metadata of over 500 million tweets and the evidence shows that the overwhelming majority of this content originates from within the borders of Iran. The study describes the scope of Iran's continued connection to the global community via Twitter, descriptively explores the content of that social media, evaluates what this means for Iranian politics and society, and explores its broader implications for researchers in the age of social media. In particular, we argue that the demonstrated ability to collect the voices of citizens, even from one of the most repressive digital regimes in the world, provides an invaluable framework for scholars with even minimal resources to undertake large-scale digital ethnography.